MANIFESTASI STRATEGI HAFALAN BERMAKNA DALAM PROGRAM TAHFIDZ SANTRI PUTRI DI PONDOK PESANTREN NURUL QUR’AN PATOKAN KRAKSAAN - Irhamni Maulana; Herawati Herawati; Yeniati Ulfah (STKIP Pesisir Selatan, 2026)
Objective: The imbalance between the Increasing quantity of memorization and the declining retention of memory and semantic understanding remains a common Issue in tahfidz programs. This condition indicates that the achievement of memorization targets and the speed of recitation submission are often prioritized over understanding the meaning of Qur’anic verses, which may r’duce the long-term quality of memorization and the internalization of Qur’anic values In students’ daily lives. This study aims to describe the implementation of a meaning-based Qur’anic learning strategy among female students at Pondok Pesantren Nurul Qur’an. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings reveal that the meaning-based memorization strategy was implemented through the use of keywords to strengthen memory, understanding Arabic grammatical structures such as nahwu, sharaf, and tajwid, as well as reinforcing students’ spiritual motivation. The strategy was proven to Improve memorization fluency, retention, and deeper comprehension of Qur’anic verses. Furthermore, the implementation of this strategy encouraged behavioral changes among students as a form of internalizing Qur’anic values in everyday life. Therefore, meaning-based memorization strategies can serve as an effective approach to improving the quality of tahfidz programs through strengthening understanding, appreciation, and practice of the Qur’an.